Demokrasi : rakyat Terengganu menolak parti Islam - Wan Nik Wan Yussof ([Kota Bharu], Kelantan Darulnaim : Political Analysis and Strategic Development, 2004)
Political issues in Terengganu on the winning party of Barisan Nasional over Parti Islam Se-Malaysia in the 2004 election.
In Malay.
Includes bibliographical references (p. 157-159) and index.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Elections -- Malaysia -- Terengganu; Democracy -- Malaysia -- Terengganu; Barisan Nasional (Organization); Parti Islam Semalaysia; Islam and politics -- Malaysia -- Terengganu